Parameters that affect the comfort level of pregnant women before cesarean section: Fasting and anxiety - Kızılkaya, Tuba; GÜL, ASİYE (ELSEVIER SCIENCE INC, STE 800, 230 PARK AVE, NEW YORK, NY 10169 USA, 2019)
Purpose: This study aimed to investigate whether fasting time and anxiety parameters affect pregnant women's preoperative comfort levels. Design: Cross-sectional descriptive study. Methods: Data were collected from pregnant women using the State-Trait Anxiety Inventory (STAI), General Comfort Questionnaire (GCQ), and Numerical Rating Scale. Findings: The mean age of the participants was 29.15 +/- 4.54 years, and the spinal anesthesia rate was 65.5%. The mean fasting time was 13.16 +/- 2.38 hours for solid food and 10.57 +/- 2.91 hours for liquid food. The mean GCQ score was 129.82 +/- 12.66, while the mean STAI subscale scores were 46.72 +/- 9.37 and 43.65 +/- 7.95. Moderately negative correlation was found between the total GCQ and STAI scores, while weak positive correlation was observed between the STAI score and the thirst sensation and mouth dryness. Conclusions: The preoperative process negatively affects comfort levels of pregnant women. Interventions that reduce the fasting time and anxiety level of pregnant women will increase comfort.
Keywords: Anxiety; Cesarean Section; Comfort; Preoperative Fasting